SAGE ESSENTIAL OIL EXHIBITS ANTIOXIDATIVE AND ANTIMICROBIAL ACTIVITY IN CHICKEN COOKED SAUSAGES - Šojić, Branislav; Škaljac, Snežana; Jokanović, Marija; Pavlić, Branimir; Eva, IVANIŠOVÁ; Monika, BOŽIKOVÁ; Savanović, Danica; BINCZARSKI, Michal (Journal on Processing and Energy in Agriculture, 2025)
Sage (Salvia officinalis L.) represents medicinal plant from Lamiaceae family, which has been recognized for various biological activities due to its complex chemical profile. Besides widely used application in pharmaceutical industry, sage has found application as flavoring agent in food products. The effect of sage essential oil (SEO) obtained from sage (Salvia officinalis L.) on antioxidative and antimicrobial activity in cooked chicken sausages was investigated. pH, instrumental parameters of color (CIE L*, CIE a* and CIE b*), thiobarbituric acid-reactive substance (TBARS) value, microbial profile and sensory panel scores were examined. The addition of SEO in concentrations from 0.010 to 0.100 µl/g significantly (p<0.05) affected the color of the product by reducing in lightness (CIE L*) and increasing in redness (CIE a*). The inclusion of SEO in concentrations of 0.075 and 0.100 µL/g significantly (p<0.05) reduced the lipid oxidation defined by TBARS test. All five tested concentrations of SEO resulted in significant (p<0.05) inhibition of bacterial growth. This study shows that the sage essential oil could be used in processing of cooked chicken sausages in order to improve oxidative and microbial stability as well as to enhance their color characteristics, without negative implications on flavor of the final meat products.